Pengenalan Peta dan Identifikasi Potensi Daerah untuk Pembuatan Peta Potensi Desa di Dusun Pisangan, Kelurahan Sumberrejo, Kecamatan Tempel, Kabupaten Sleman - Yoga Ade P; Diah Ayu Putri K; Bagus Dananjaya; Damar Firmansyah; Helpi Widia A; Lusiana Chania; M. Rizqi Mahardika S; Hari Marwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
The potention of a village can be seen in the form of a map when the map comes with a description of the land resources and human resources as the backbone of the rural economy. Land resources can be reflected in the distribution of land use in the village, while the human resources can be illustrated by the small industries or existing SMEs. Map existing describes village areas and sometimes the picture were draw by a person who know the areas. Village map usually contains location or the location of the village facilities, roads, rivers and boundaries hamlet/ RW or village limits. Moreover village map always displays information surrounding neighboring villages. Deficiencies that exist in a map of the village is likely to occur because of the knowledge map-making has not been fully understood by the individual who made the map. It could provide wrong and not information accurate for people whose using the village map. Purpose of this activity is to provide knowledge about the knowledge map to participants. While the purpose of the activities of Community Services were to provide knowledge about the map and the identification of potential rural village in the manufacture of Potential Map. The implementation of the Community Services with interactive discussions by Focus Group Discussion. FGDs were conducted as a way to confirm the village boundaries, facilities and potential village. Community Services activities result were that participants have understood the potential of the village and the knowledge base map. In addition it has arranged a map of Potential Rural Dusun Pisangan, Kelurahan Sumberejo, Kecamatan Tempel, Kabupaten Sleman. The map has been handed over to the village and their representatives - each elementary school in the two villages.